2003
DOI: 10.1074/jbc.m209276200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Collagen XVIII and Localization of Its Glycosaminoglycan Attachment Sites

Abstract: Collagen XVIII is the only currently known collagen that carries heparan sulfate glycosaminoglycan side chains. The number and location of the glycosaminoglycan attachment sites in the core protein were determined by eukaryotic expression of full-length chick collagen XVIII and site-directed mutagenesis. Three SerGly consensus sequences carrying glycosaminoglycan side chains were detected in the middle and N-terminal part of the core protein. One of the Ser-Gly consensus sequences carried a heparan sulfate sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 28 publications
1
45
0
1
Order By: Relevance
“…Collagen XVIII has attracted much interest on several accounts. It has the structural properties of both a collagen and a proteoglycan (2); it contains the antiangiogenic molecule, endostatin (3), and its coding gene, collagen α1 (XVIII) (COL18A1), is mutated in the rare, recessively inherited Knobloch syndrome (4). This condition is characterized by high myopia and vitro-retinal degeneration, and occasionally by occipital encephalocele (5,6).…”
mentioning
confidence: 99%
“…Collagen XVIII has attracted much interest on several accounts. It has the structural properties of both a collagen and a proteoglycan (2); it contains the antiangiogenic molecule, endostatin (3), and its coding gene, collagen α1 (XVIII) (COL18A1), is mutated in the rare, recessively inherited Knobloch syndrome (4). This condition is characterized by high myopia and vitro-retinal degeneration, and occasionally by occipital encephalocele (5,6).…”
mentioning
confidence: 99%
“…Finally, clusters 1 and 2 are conserved between the available agrin cDNA sequences from ray, rat, human, and chick. The interspecies conservation of SG consensus sequences turned out to be the best predictor for GAG glycosylation in collagen XVIII (8). We are therefore confident that the only GAG attachment sites of agrin are the ones detected in the two SG clusters.…”
Section: Constructmentioning
confidence: 62%
“…In collagen XVIII, however, it was only the first serine in a cluster of 3 SGs that was glycosylated. The second serine in the collagen XVIII SG cluster was only important to direct the glycosylation for HS instead of CS, and the third SG was not important to GAG priming at all (8). An effect of adjacent SGs on the type of GAG glycosylation was not observed for the first multiple SG site (PF9) since the GAG side chains remained the same after mutations of the adjacent serines.…”
Section: Constructmentioning
confidence: 87%
See 1 more Smart Citation
“…The aorta is an abundant tissue source of the heparan sulfate proteoglycan (PG) collagen XVIII and its proteolytically released endostatin (ES) fragment, which has previously been shown to inhibit angiogenesis in cancer and atherosclerosis models [37]. The ES portion of collagen XVIII has no attachment sites for GAG but has high affinity for heparin, which is necessary for its antiangiogenesis functions [38]. A recent data has shown that collagen XVIII is differentially degraded in blood vessels affected by atherosclerosis.…”
Section: Therapies Based On Response-to-retention Hypothesismentioning
confidence: 99%